1. By inspection: RHS = 2^n * 3^n * 4^n * ... * (n+1)^n
LHS = 2^n * 3^(n-1) * 4^(n-1) * 5^(n-2) * 6^(n-2) * ... * (2n-1) * 2n
= 2^n * [3^(n-1) * 2n] * [4^(n-1) * (2n-1)] * [5^(n-1) * (2n-2)^2] * [4^(n-1) * (2n-3)^2] * ...
Arranged this way you cna see that each part of the LHS is no less that the right hand side and atleast one of them is greater (n >=2), so LHS> RHS
2. Expanding the left hand side will give you 2^n terms (1 + x1 + x2 + ... + xn + x1x2 + x1x3 + ... + x1xn + x2x3 + x2x4 + ... + x2xn + .... + x1x2x3...xn), the product of these terms is equal to
(x1*x2*x3*...*xn)^(2^(n-1)) = 1 then apply the AM-Gm inequality (prove it if you need to you only need it for the case where the number of terms is a power of 2)
3. think you mean 0 <= xk < 1 instead of 0<= xk < 0. This should be a simple induction. remember that the LHS is always between 0 and 1.
4. You sure you got the sign the correct way round? for x > 0
let f(x) = (1 + x + x^2 + ... + x^ n )/ (1 + x + x^2 + ... + x^(n+1) )
= 1 + [ x^n / (1 + x + x^2 + ... + x^(n+1))]
= 1 + 1/[1/x + 1/x^2 + 1/x^3 + ... + 1/x^n]
now it is pretty clear that 1/x, 1/x^2, ... 1/x^n all decrease as x increases and they are all positive , their sum also decreases hence f(x) is an increasing function. It follows that
(1+ a + a^2 + ... + a^(n+1))/(1+ a + a^2 + ... + a^(n)) > (1+ b + b^2 + ... + b^(n+1)) / (1+ b + b^2 + ... + b^(n))